The costs of open access publication: a case study at Catalan universities - Borrego, Ángel; Anglada, Lluís (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2024)
This article explores the financial dynamics of open access (OA) publication in Catalan universities by combining four data sources: publication data coupled with article processing charge (APC) estimates; information on journal subscriptions, transformative agreements and APC payments made by universities; acknowledgements of APC funding sources in OA scholarly outputs; and a survey of authors. The findings reveal a consistent increase in OA publication across Catalan universities, with 60% of the articles indexed in the Web of Science being published in either gold or hybrid OA in 2022. In parallel, investment in the research publishing system shows an upward trend. Resources allocated to journal subscription licenses have been redirected towards transformative agreements, leading to a rise in hybrid OA publications. Additional budget allocations have been made to accommodate APCs for gold OA journals. Authors employ varied funding sources for gold and hybrid OA, with university funding programmes and research grants commonly facilitating gold OA, while transformative agreements often support hybrid OA. Authors associated with Catalan universities frequently benefit from funding schemes and transformative agreements that are accessible to their coauthors. However, survey responses underscore the multifaceted nature of researchers’ financial support, including personal assets and waivers. Authors express frustration with the evolving OA landscape, particularly concerning the exorbitant publication fees. Nevertheless, the allure of high-impact journals and expedited peer review processes continues to incentivize authors towards gold OA. Researchers voice concerns regarding the lack of equitable funding programmes and potential conflicts of interest within gold OA models, which signals the risk of compromising peer review integrity to prioritize profits. This study underscores the need for further research to deepen our understanding of scholarly publishing expenditure and inform strategies for fostering a sustainable, equitable OA ecosystem.